CONTEMPORARY APPROACHES TO THE STUDY OF KHOREZM ETHNOGRAPHY AND THE SCIENTIFIC CONTRIBUTION OF FEMALE SCHOLARS (CASE OF THE INDEPENDENCE PERIOD) - Normetova Mahfuza Alisher qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  provides  a  general  analysis  of  contemporary  studies conducted in the field of Khorezm ethnography during the years of independence. The research examines scientific works devoted to the ethnic and cultural heritage of the oasis,  folk  traditions,  customs,  rituals,  national  clothing  and  jewelry  traditions, gastronomic and dance culture, wedding ceremonies, as well as the distinctive features of Turkmen communities. Particular attention is paid to the scientific contributions of women scholars, whose research has played a significant role in the development of Khorezm ethnography.